2019
DOI: 10.1016/j.scog.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Neurological soft signs (NSS) and cognitive impairment in chronic schizophrenia

Abstract: Recent studies indicate that neurological soft signs (NSS) in schizophrenia are associated with generalized cognitive impairments rather than changes in specific neuropsychological domains. However, the majority of studies solely included first-episode patients or patients with a remitting course and did not consider age, course, education or severity of global cognitive deficits as potential confounding variables. Therefore, we examined NSS with respect to cognitive deficits in chronic schizophrenia, i.e. pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 77 publications
3
16
0
2
Order By: Relevance
“…While the respective studies—among them probably the first fMRI study in schizophrenia (6) and a single longitudinal trail (8)—solely included patients with schizophrenia, results suggest that NSS refer to disseminated changes in the whole motor system in particular a cerebello-thalamo-prefrontal network (9) rather than to deficits in discrete cerebral sites. Similarly, NSS are associated with a wealth of cognitive deficits ranging from attention/psychomotor speed and executive dysfunctions to complex neuropsychological abilities, such as logical memory, autobiographic episodic memory, and theory of mind (10).…”
mentioning
confidence: 99%
“…While the respective studies—among them probably the first fMRI study in schizophrenia (6) and a single longitudinal trail (8)—solely included patients with schizophrenia, results suggest that NSS refer to disseminated changes in the whole motor system in particular a cerebello-thalamo-prefrontal network (9) rather than to deficits in discrete cerebral sites. Similarly, NSS are associated with a wealth of cognitive deficits ranging from attention/psychomotor speed and executive dysfunctions to complex neuropsychological abilities, such as logical memory, autobiographic episodic memory, and theory of mind (10).…”
mentioning
confidence: 99%
“…Interestingly, it has been shown that learning motor sequences requires the involvement of bilateral superior and anterior prefrontal cortex, right superior temporal cortex and left cerebellum [68]. Along with this, we recently described that NSS reflect a rather wide range of cognitive deficits in schizophrenia [69], a finding that may additionally explain the involvement of frontal and temporal sites.…”
Section: Plos Onementioning
confidence: 63%
“…Indeed, initial perceptual deficits, working memory impairments, or encoding disorder have been thought to explain patients’ memory impairments. A more recent study also pointed out that neurological soft signs might be correlated with autobiographical memory performance (58). Future studies using wearable cameras or virtual reality could provide new insights on the role of those factors, as they enable to control and manipulate the to-be-encoded event.…”
Section: Discussionmentioning
confidence: 98%